Web-Based Assignment Management System Application Design to Increase Personnel Productivity and Effectiveness in Product Documentation Division: Rancang Bangun Aplikasi Sistem Manajemen Penugasan Berbasis Web Guna Meningkatkan Produktifitas dan Efektifitas Personel Bagproddok Dispenad - Seftian Candra Pratama; Eryan Ahmad Firdaus; Rochedi Idul Adha (NUANSA INFORMATIKA, 2025)
An effective task management is essential for enhancing productivity and operational efficiency within organizations. Currently, the Production Documentation Division of the Information Service of the Indonesian Army (Dispend) uses WhatsApp for task coordination, which results in fragmented communication, limited tracking, and reduced transparency. To overcome these issues, this study develops a web-based assignment management system  to improve task distribution, monitoring, and reporting. The system is built using the Rapid Application Development (RAD) model, which emphasizes iterative prototyping and users’ feedback. Key features include task creation, progress tracking, file submission, approval workflows, and reporting tools, supported by role-based access control for both administrators and users. The implementation of this system shows significant improvements in workflow efficiency, transparency, and accountability compared to the previous WhatsApp-based method. In conclusion, the system contributes to better documentation, timely task completion, and enhanced collaboration, thereby increasing overall productivity. Future enhancements may include mobile integration and real-time notifications to further improved accessibility and operational effectiveness.